Mechanisms of sorafenib-induced cardiotoxicity: ER stress induces upregulation of ATF3, leading to downregulation of NDUFS1 expression and mitochondrial dysfunction - Yan, Ming; Peng, Cheng; Lang, Xueyan; Li, Yilan; Zhang, Yao (Frontiers in Pharmacology, 2025)
BackgroundSorafenib, a widely used tyrosine kinase inhibitor (TKI), has been associated with cardiotoxic effects; however, the precise molecular basis of this toxicity remains incompletely characterized. This study examined sorafenib’s impact on cardiac cells, focusing on endoplasmic reticulum (ER) stress signaling, specifically the PERK-eIF2α-ATF4 pathway and its downstream network.MethodsTo elucidate these mechanisms, we employed a comprehensive approach integrating in vivo rat models, H9C2 cell-based assays, transcriptomic and proteomic profiling, along with biochemical validation techniques.ResultsOur study reveals that sorafenib compromises cardiac function by inducing ER stress in cardiomyocytes, which activates the PERK-eIF2α-ATF4 pathway, leading to mitochondrial damage and apoptosis. These outcomes were supported by Western blot analysis and microscopic imaging, and were significantly mitigated following treatment with the ER stress inhibitor GSK2606414. Transcriptome data highlighted activating transcription factor 3 (ATF3) as the most prominently induced gene post-treatment. Further enrichment analysis identified several related pathways, while RT-PCR and immunoblotting confirmed ATF3 upregulation in H9C2 cells. Proteomic screening revealed NDUFS1 as a potential downstream effector. Silencing ATF3 via siRNA partially restored mitochondrial function, suggesting a negative regulatory effect of ATF3 on NDUFS1 that contributes to sorafenib-induced mitochondrial impairment.ConclusionCollectively, these results uncover a critical signaling cascade—PERK/eIF2α/ATF4/ATF3/NDUFS1—involved in sorafenib-mediated cardiotoxicity and point to ATF3 modulation as a promising target for preventing or reducing cardiac injury caused by this drug.